QUALITY MANAGEMENT TOOLS AND THEIR IMPORTANCE FOR THE DEVELOPMENT OF ORGANIZATIONS - Henrique Correa Braga, Bruno; Midori Yada de Almeida, Marcela (Revista Interface Tecnológica, 2021)
Within a highly competitive market with increasingly demanding customers, ensuring quality goods and products has been an important strategy for the growth of organizations. The quality tools serve as a guide so that some processes are always carried out as a way to ensure continuous improvement, allowing companies to offer quality goods or services. The purpose of this article is to bring some quality tools, highlighting their importance for the growth of organizations. The methodology used was a literature review. The results found in the literature affirm the importance of using quality tools, and describe that companies saw ample growth after adding quality to their businesses. Through this article it was possible to conclude that, given quality as an important factor and provider of growth, the use of tools is an important alternative and should be used according to the needs of the company and its customers.
Keywords: Quality.; Tool.; Organizations.; Growth.